Dakwah dan Pengembangan Kendali Diri: Upaya Antisipasi Kecenderungan Seks Bebas Remaja - Tajiri, Hajir (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
Daâwah in context preventing of freesexual behavior on teenager is something not easy. Daâwah in this context need creative efforts either individual or collective andÂ collaborative of all profesion and government policy. One of suitable approach is cognitive-behavioral, with this approach estimated will able giving solution to teenager problem, especially to increase self control ability as prevention stepÂ to freesexual tendency. That is by cognition restructurization or modification and rebuild their behavior.